Collective narcissism moderates the effect of in-group image threat on intergroup hostility - Golec de Zavala, A. (2013)
Results of 4 experiments demonstrated that under in-group image threat collective narcissism predicts retaliatory intergroup hostility. Under in-group criticism (vs. praise) collective narcissists expressed intention to harm the offending out-group but not other, nonoffending out-groups. This effect was specific to collective narcissism and was replicated in studies that accounted for the overlap between collective narcissism and individual narcissism, in-group positivity (in-group identification, blind and constructive patriotism), social dominance orientation, and right wing authoritarianism. The link between collective narcissism and retaliatory intergroup hostility under in-group image threat was found in the context of national identity and international relations and in the context of a social identity defined by university affiliation. Study 4 demonstrated that the relationship between collective narcissism and intergroup hostility was mediated by the perception of in-group criticism as personally threatening. The results advance our understanding of the mechanism driving the link between collective narcissism and intergroup hostility. They indicate that threatened egotism theory can be extended into the intergroup domain.